Patogenicidade de espécies de monosporascus em meloeiro - Gomes, Thomaz Rauan Rodrigues (Universidade Federal Rural do Semi-Árido, 2019)
Monosporascus cannonballus vine decline is one of the main root diseases in cucurbits in Brazil and worldwide. Phylogenetic studies conducted with Brazilian isolates obtained from melon production fields in the Agropole RN/CE region culminated with the identification of five new Monosporascus species. With the need to study the virulence of these new species, this work aimed to verify the pathogenicity of seven Monosporascus species in melon. The experiment was carried out in a greenhouse with seven species of Monosporascus (M. brasiliensis-CMM4839, M. caatinguensis-CMM4833, M. cannonballus-CMM2429, M. eutypoides-MT45, M. mossoroensis-CMM4857, M. nordestinus-CMM4846 and M. semiaridus-CMM4830) and a negative control. Inoculation was performed by adding 10 mL of mycelium suspension with 2,5 x 102 UFC mL-1 per vase five days before transplanting the seedlings. The vases were filled with a mixture of autoclaved soil + Tropstrato® (2: 1). Melon seedlings cv. „Gold mine‟ with 10 days after sowing (DAS) were transplanted to the inoculated vases. At 40 days after transplanting, the following variables were evaluated: severity (diagrammatic grading scale), incidence, plant height (PH), root length (RL), shoot fresh weight (SFW), shoot dry weight (SDW), root fresh weight (RFW) and root dry weight (RDW). The experiment was conducted in a completely randomized design, consisting of treatments represented by the negative control and the Monosporascus species, with six replications. Severity and incidence of the disease were analyzed by the Kruskal–Wallis test. For PH, RL, SFW, RFW, SDW and RDW the data were submitted to variance analysis and the means compared by Tukey test. There was a statistical difference for all variables analyzed in the evaluated culture. All Monosporascus isolates were pathogenic to melon. M. eutypoides differed statistically from the control, presenting higher mean in severity, while M. brasiliensis obtained lower mean severity compared to the control. All Monosporascus species differed from control in incidence. The M. caatinguensis species presented the lowest average for PH, while the M. eutypoides species presented the lowest average for RL, SFW, RFW and SDW. For SFW the species Monosporascus cannonballus and Monosporascus eutypoides provided the lowest mean for this variable analyzed.
Monografia
Keywords: Cucumis melo L.; Declínio de ramas; Patógenos radiculares; Cucumis melo L.; Root pathogens; Vine decline; CIENCIAS AGRARIAS::AGRONOMIA